Altered GABAA receptor density and unaltered blood–brain barrier [11C]flumazenil transport in drug-resistant epilepsy patients with mesial temporal sclerosis. Issue 1 (January 2017) - Froklage, Femke E; Postnov, Andrey; Yaqub, Maqsood M; Bakker, Esther; Boellaard, Ronald; Hendrikse, N Harry; Comans, Emile FI; Schuit, Robert C; Schober, Patrick; Velis, Demetrios N; Zwemmer, Jack; Heimans, Jan J; et al.
Studies in rodents suggest that flumazenil is a P-glycoprotein substrate at the blood–brain barrier. This study aimed to assess whether [ 11 C]flumazenil is a P-glycoprotein substrate in humans and to what extent increased P-glycoprotein function in epilepsy may confound interpretation of clinical [ 11 C]flumazenil studies used to assess gamma-aminobutyric acid A receptors. Nine drug-resistant patients with epilepsy and mesial temporal sclerosis were scanned twice using [ 11 C]flumazenil before and after partial P-glycoprotein blockade with tariquidar. Volume of distribution, nondisplaceable binding potential, and the ratio of rate constants of [ 11 C]flumazenil transport across the blood–brain barrier (K1 /k2 ) were derived for whole brain and several regions. All parameters were compared between pre- and post-tariquidar scans. Regional results were compared between mesial temporal sclerosis and contralateral sides. Tariquidar significantly increased global K1 /k2 (+23%) and volume of distribution (+10%), but not nondisplaceable binding potential. At the mesial temporal sclerosis side volume of distribution and nondisplaceable binding potential were lower in hippocampus (both ∼−19%) and amygdala (both ∼−16%), but K1 /k2 did not differ, suggesting that only regional gamma-aminobutyric acid A receptor density is altered in epilepsy. In conclusion, although [ 11 C]flumazenil appears to be a (weak) P-glycoprotein substrate in humans, this does not seem to affect its role as a tracer for assessing gamma-aminobutyric acid A receptor density.